Improved ionic conductivity and efficiency of dye-sensitized solar cells with the incorporation of 1-methyl-3-propylimidazolium iodide - Tan, Chee Yu; Saidi, Norshahirah Mohamad; Farhana, N.K.; Omar, Fatin Saiha; Algaradah, Mohammed M.; Bashir, Shahid; Ramesh, Subramaniam; Ramesh, Kasi (Springer Verlag (Germany), 2020)
1-Methyl-3-propylimidazolium iodide (MPII) ionic liquid incorporated gel polymer electrolyte (GPE) has successfully enhanced the efficiency of a dye-sensitized solar cell (DSSC). A series of gel polymer electrolytes containing different amounts of MPII were prepared and characterized. A maximum ionic conductivity of 3.99 mS cm−1 was obtained in a GPE containing 10 wt% MPII, which was accompanied by the lowest activation energy. The results from dielectric studies showed typical behaviour for both ɛ’ and ɛ” in which their values decreased with increasing frequency but increased proportionately with temperature. From the results of FESEM, the morphologies of the GPE became slightly rougher after the addition of MPII. Dye-sensitized solar cells were fabricated and characterized using electrochemical impedance spectroscopy (EIS) and photovoltaic studies. DSSC with the best performance (4.35% of efficiency, 9.97 mA cm−2 of JSC, 0.67 V of VOC, and 65.39% of fill factor) was assembled using the GPE with 10 wt% of MPII. © 2020, Springer-Verlag GmbH Germany, part of Springer Nature.